Gradient Multilayer Design of Ti3C2Tx MXene Nanocomposite for Strong and Broadband Microwave Absorption - Yajun Zhang; Long Pan; Peigen Zhang; ZhengMing Sun (Small Science, 2022)
High‐performance electromagnetic (EM) absorbing materials are in urgent need due to severe EM pollution caused by fast development of communication technology and electronic devices. Gradient structure benefits EM absorbing performance. However, the relevant study is very limited, and the relationship between component layers and overall performance is unclear. Herein, a gradient structure containing impedance matching layer, lossy layer, and reflective layer is built via repeated casting‐drying method using Ti3C2Tx MXene and polyvinyl alcohol. With optimized gradient structure, the minimum reflection loss (RL) reaches −74.8 dB with effective absorbing bandwidth (EAB) covering the whole X‐band. The good absorbing performance is ascribed to the good impedance matching, which is derived from the stepwisely increased permittivity of each layer. Moreover, it is found that RL reaches the lowest value when lossy layer permittivity is close to the average permittivity of impedance matching layer and reflective layer. In addition, the decrease of lossy layer permittivity causes the decrease of total thickness of the gradient structure. This work demonstrates the effectiveness of gradient structure toward strong and broadband microwave absorption and provides rules for designing proper gradient structures to satisfy different requirements.